The relationship between central bank transparency and the quality of inflation forecasts: is it U-shaped? - Emna Trabelsi (Economics and Econometrics Research Institute (EERI), 2012)
A recent theoretical literature highlighted the potential dangers of further increasing information disclosure by central banks. This paper gives a continuous empirical investigation of the existence of an optimal degree of transparency in the lines of van der Cruijsen et al. We test a quadratic relationship between central bank transparency and the inflation persistence by introducing some technical and economic modifications. Particularly, we used three new measures of transparency. An appropriate U shape test that was made through a Stata routine, recently developed by Lind and Mehlum, indicates a robust optimal intermediate degree of transparency, but its level is not. These results were obtained using a panel of 11 OECD central banks under the period 1999-2009. The estimations were run using a bias corrected LSDVC, a newly recent technique developed by Bruno for short dynamic panels with fixed effects, extended to accommodate unbalanced data.
Keywords: C23; E58; 330; Intermediate optimal transparency degree; inflation forecasts; inflation persistence; u-shaped relationship; non linear modeling; LSDVC; Principal Component Analysis